Is More Entrepreneurship better? - Philipp Koellinger; Christian Roessler (Tinbergen Institute, 2009)
We develop a new perspective on the boundary of the firm that is consistent with the empirical observation that the share of entrepreneurs first decreases and then increases in the course of economic development. Existing theory based on transaction costs is difficult to relate to these well-established dynamics. Our approach focuses on changing incentives to specialize and adapt, in order to access complementarities that arise from diverse abilities and access to wealth. We discuss why the efficient number of entrepreneurs is bounded and changes in the course of economic development.
Keywords: L26; D20; J24; O10; 330; Entrepreneurship; theory of the firm; organizations; economic development; Entrepreneurship-Ansatz; Unternehmensgründung; Unternehmensorganisation; Transaktionskosten; Theorie der Unternehmung